Genotype and within-pod bean position microenvironment effect on seed choice for raising cocoa (Theobroma cacao L.) seedlings - Daniel B. ADEWALE; Beatrice A. NDUKA (Acta Agriculturae Slovenica)
The probable role of within-pod microenvironment on seed sizes, seedling vigour and biomass yield of four cocoa genotypes was investigated for two years. The respective main, sub and sub-sub plots in the split-split plot experimental design were years, genotypes and within-pod bean positions. Data were taken on cocoa bean length, width and thickness after each pod was opened. Four weekly periodic data were obtained for plant height (PH), stem girth (SG) and number of leaves (NOL); root and shoot biomass yield were also recorded. Analysis of variance revealed significant (p ≤ 0.05) bean position, genotypes, years and some interaction on the studied traits. Means of the levels of the three factors differed significantly (p ≤ 0.05). Proximal, middle and distal positions were distinct within-pod microenvironments. The pod middle cavity housed the longest, widest and heaviest beans. Trend analysis of the growing sequences of NOL, PH and SG by the four genotypes differed with bean locations. For bean length, GGE biplot respectively identified CRIN Tc1, CRIN Tc2 and CRIN Tc3 as the best genotype for middle, proximal and the distal positions. The intra-locular space within the pod enhanced differential seed development and maturation; this was evident in the seedling vigour.